Some Remarks on the Advantages and Disadvantages of Huizinga’s Concept of Play in Current Debates: By Way of Introduction - Hanssen, Léon (Into the Magic Circle: Rethinking Homo Ludens, 2024)
As an introduction to the online and open access journal Into the Magic Circle, the editor-in-chief Léon Hanssen offers some observations which primarily focus on Johan Huizinga’s basic assumptions about the play element of culture and their relevance in contemporary culture. What makes Huizinga's thesis in Homo Ludens (1938) so challenging and fitting as a source of inspiration, whilst at the same time so debatable, and perhaps even outdated with regard to contemporary culture?